DNA methylation aberrancies as a guide for surveillance and treatment of human cancers - Gangning Liang; Daniel J. Weisenberger (Epigenetics, 2017)
DNA methylation aberrancies are hallmarks of human cancers and are characterized by global DNA hypomethylation of repetitive elements and non-CpG rich regions concomitant with locus-specific DNA hypermethylation. DNA methylation changes may result in altered gene expression profiles, most notably the silencing of tumor suppressors, microRNAs, endogenous retorviruses and tumor antigens due to promoter DNA hypermethylation, as well as oncogene upregulation due to gene-body DNA hypermethylation. Here, we review DNA methylation aberrancies in human cancers, their use in cancer surveillance and the interplay between DNA methylation and histone modifications in gene regulation. We also summarize DNA methylation inhibitors and their therapeutic effects in cancer treatment. In this context, we describe the integration of DNA methylation inhibitors with conventional chemotherapies, DNA repair inhibitors and immune-based therapies, to bring the epigenome closer to its normal state and increase sensitivity to other therapeutic agents to improve patient outcome and survival.